2016
DOI: 10.1016/bs.mie.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

BioID Identification of Lamin-Associated Proteins

Abstract: The nuclear lamina is primarily composed of type-V intermediate filaments, the A- and B-type lamins, which give mechanical support to the nuclear envelope, contribute to heterochromatin organization and regulate a myriad of nuclear processes. Over a dozen human diseases, collectively named laminopathies, are associated with mutations in the genes that encode the nuclear lamins. Although the etiology of the laminopathies is well understood, the molecular mechanisms by which they lead to disease remain unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…Once they reached approximately 80% confluency, they were grown in the presence of 50 μM biotin overnight (minimum of 8 hr). Biotinylated proteins were purified as previously described (Mehus, Anderson, & Roux, ). Briefly, cells were lifted from the plate using 0.25% trypsin EDTA, and washed with PBS via centrifugation (700 g , 4 °C, 10 min).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once they reached approximately 80% confluency, they were grown in the presence of 50 μM biotin overnight (minimum of 8 hr). Biotinylated proteins were purified as previously described (Mehus, Anderson, & Roux, ). Briefly, cells were lifted from the plate using 0.25% trypsin EDTA, and washed with PBS via centrifugation (700 g , 4 °C, 10 min).…”
Section: Methodsmentioning
confidence: 99%
“…Biotinylated proteins were purified as previously described (Mehus, Anderson, & Roux, 2016 (1:5,000, ThermoFisher) for 40 min, and then washed in PBS three times for 5 min. Blots were then exposed to Clarity ECL (Bio-Rad) for 5 min, and visualized using the BioRad ChemiDoc MP imager.…”
Section: Streptavidin Pulldownmentioning
confidence: 99%
“…We have modified the promiscuous biotin ligase tagging system (85)(86)(87)(88) to analyze the protein interaction networks of the G12D, WT, S17N, and C185S/G12D K-Ras proteins. As shown, our chimeric BirA*Ras proteins were expressed as expected, localized as predicted, and their localization patterns matched the patterns of the proteins they biotinylated (Figures 1-4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified proteins enriched at the nuclear lamina (the "laminome") through multiple methods, including BioID [21][22][23][24][25] . Here we use BioID with BioSITe (BioID coupled with biotinylation site enrichment and analysis) to measure protein-protein interactions of the INM protein Lap2β (Figure 2) in MEFs and integrate these with the previous laminome findings to generate an enhanced INM/lamina proteome map [21][22][23]27,28,36,37] .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…These coiled-coil domain proteins provide a structural scaffold at the INM, with the A-type lamins being shown to mediate LAD organization [12,[17][18][19] . Longstanding efforts have been undertaken to map and characterize the local proteome of the nuclear lamina of the INM using inner nuclear membrane preparations, co-immunoprecipitation and, more recently, BioID ( Bio tinylation Id entification), a method for detecting proximal protein interactions in living cells [21][22][23][24][25] . However, these efforts have exclusively focused on protein members of the INM/lamina as baits and have not measured the protein landscape of LADs themselves or the intersection of these proteome environments.…”
Section: Introductionmentioning
confidence: 99%